Analysis of Live Shopping Strategy on TikTok Application as a Marketing Tool for Majalaya Sarong Wholesalers - Azzahra, Salma; Chandrawijaya, Michael (Dinasti Publisher, 2025)
This study aims to evaluate the Live Shopping strategy used by Grosir Sarung Majalaya in marketing products through TikTok Shop. This study uses a qualitative approach with triangulation techniques in the form of interviews and observations to identify key elements in digital marketing strategies, such as broadcast scheduling, product selection, interaction with consumers, and providing exclusive promotions. The results of the study show that the TikTok Live Streaming feature is effectively used as a means of direct communication that can expand market reach and build closeness with audiences digitally.